Calculation of matrix elements of π± -meson scattering byHeisotopesin the Glauber theory - Имамбеков, О.; Токсаба, Ж. (Recent Contributions to Physics, 2018)
Within the framework of the Glauber diffraction theory calculated scattering matrix elements of π-mesons isotopes helium nucleus: 6He and 8He. The interaction π-mesons with nuclei are presented as a series of multiple scattering. This approach allows for such processes explicitly take into account the multiplicity of different collisions and their contribution to the total differential cross section for the reaction. For a description of the internal state of the 6He nucleus using well proven realistic three-particle wave function in αnn-model, and for the 8He nucleus - shell function with a large basis. It is important to note that withthis approach it is possible to calculate all matrix elements analytically without any simplifications, and thus without loss of accuracy inevitablefor numerical integration.